Shexiang Baoxin Pill, a Traditional Chinese Herbal Formula, Rescues the Cognitive Impairments in APP/PS1 Transgenic Mice - Hu, Wei-Hui; Mak, Shing-Hung; Zheng, Zhong-Yu; Xia, Ying-Jie; Xu, Miranda Li; Duan, Ran; Dong, Tina Ting-Xia; Li, Shao-Ping; Zhan, Chang-Sen; Shang, Xiao-Hui; Tsim, Karl Wah-Keung (Frontiers in Pharmacology, 2020)
Background: Shexiang Baoxin Pill (SBP), a formulated traditional Chinese medicine (TCM), has been widely used to treat cardiovascular diseases for years. This herbal mixture has been shown to promote differentiation of cultured neuronal cells. Here, we aimed to investigate the effects of SBP in attenuating cognitive impairment in APP/PS1 transgenic mice. Methods: Ethanol and water extracts of SBP, denoted as SBPEtOH and SBPwater, were standardized and applied onto cultured rat pheochromocytoma PC12 cells. The potential effect of SBPEtOH extract in attenuating the cognitive impairments in APP/PS1 transgenic mice was shown by following lines of evidence: (i) inhibition of Aβ fibril formation, (ii) suppression of secretions of cytokines, and (iii) improvement of behavioural tests by Morris water maze. Results: SBPwater and SBPEtOH inhibited the formation of β-amyloid fibrils and protected the Aβ-induced cytotoxicity in cultured PC12 cells. In APP/PS1 transgenic mice, the treatment of SBPEtOH inhibited expressions of NO, NOS, AChE, as well as aggregation of Aβ. Besides, the levels of pro-inflammatory cytokines were suppressed by SBP treatment in the transgenic mice. Importantly, the behavioral tests by Morris Water maze indicated that SBP attenuated cognitive impairments in APP/PS1 transgenic mice. Conclusion: The current result has supported the notion that SPB might ameliorate the cognitive impairment through multiple targets, suggesting that SBP could be considered as a promising anti-AD agent.